Powerful communication skills : - McKenna, Colleen (Career Press, 1998)
Powerful Communication Skills will show users how to speak clearly, listen accurately, and assert oneself effectively. Developing powerful methods of sharing information - whether it's reading, writing, speaking, or listening - will result in higher self-esteem, clearer communication and a powerful professional image.Written in an easy to follow format, this guide shows how to bridge communication gaps, how to clearly ask for infomation needed, and how to deal more effectively with challenges. With easy-to-implement tips, users can immediately incorporate the content.